Pengembangan Instrumen Penilaian Autentik Berbasis PBL Pada Materi Dampak Pencemaran Bagi Kehidupan Di Sekolah Menengah Pertama - Timma Dormauli Siallagan; Syamsurizal Syamsurizal; Bambang Hariyadi (Universitas Jambi, 2016)
The purpose of this developmental research was to develop a scientific approach based science worksheet on the dynamic electrical material topic for ninth-grade junior high school students. The worksheet were developed based on scientific approach. The stages include: observing, asking questions, gathering information, processing information, and communicating. The development model used is the 4-D Model consists of 4 stages: define, design, develop, and desimanate. The results of the validation, a small and large group trials indicated that the used of the scientific approach based science worksheet was appropriate for use. Thus, the developed worksheets can be used in the process of learning for Junior high school science students. Keywords : Worksheet , Scientific approach